Penyusunan Bahan Pembelajaran Kompilasi Bagi Pengajar di SMK Negeri 1 Cibinong, Bogor Jawa Barat - Rusmono; Wisnu Djatmiko (Bahasa Indonesia, 2022)
Abstract In general, the form of learning at SMK Negeri I Cibinong Bogor is classroom learning using learning strategies and learning materials that refer to learning objectives. The competence of teachers in developing learning materials is considered to be still low, so it is necessary to make a training on Compilation of Compilation Learning Materials for teachers at SMK Negeri 1 Cibinong Bogor. The training was carried out using the method of applying science and technology directly to 55 teachers of public and private vocational schools in Cibinong Bogor using the Zoom application. The training was carried out in two sessions, namely: (1) discussing learning materials as a system, instructional analysis, setting specific instructional objectives, developing learning-outcome test instruments, developing learning strategies; and session (2) discusses theoretical concepts in developing compiled learning materials, preparing syllabus for one semester of subjects, the concept of making pieces of learning materials based on ICT for one semester, compiling pieces of learning materials based on ICT for subjects taught and making slides with MsPowerpoint, and then participants were asked to deliver Compiled Learning Materials complete with slides using MsPowerpoint. The results of the training showed that, in general, the teachers who participated in the training were still not maximal in mastering the following materials: (1) Instructional Analysis; (2) Develop Specific Instructional Objectives (ICT); (3) Developing Learning Outcomes Test Instruments; (4) and Developing Learning Strategies, so that the training objectives for the preparation of Compilation Learning Materials for 55 MPGP Electronics Engineering teachers conducted at SMK Negeri 1 Cibinong Bogor have not been maximally achieved. Abstrak Secara umum, bentuk-pembelajaran di SMK Negeri I Cibinong Bogor adalah pembelajaran di kelas menggunakan strategi-pembelajaran dan bahan-pembelajaran yang mengacu dengan tujuan pembelajaran. Kompetensi-guru dalam mengembangkan bahan pembelajaran dianggap masih rendah, sehingga perlu dibuat suatu pelatihan Penyusunan Bahan Pembelajaran Kompilasi untuk guru-guru di SMK Negeri 1 Cibinong Bogor. Pelatihan dilakukan menggunakan metode penerapan IPTEKS secara langsung ke 55 orang guru SMK Negeri dan Swasta di Cibinong Bogor menggunakan aplikasi Zoom. Pelatihan dilaksanakan dalam dua-sesi, yaitu: (1) membahas materi pembelajaran sebagai sistem, analisis instruksional, menyusun tujuan instruksional khusus, mengembangkan instrumen tes hasil-belajar, mengembangkan strategi pembelajaran; dan sesi (2) membahas konsep teori dalam pengembangkan bahan pembelajaran kompilasi, menyiapkan silabus mata-pelajaran satu semester, konsep membuat penggalan-penggalan bahan pembelajaran berdasarkan TIK untuk satu semester, menyusun penggalan bahan pembelajaran berdasarkan TIK mata pelajaran yang diampu dan membuat slide dengan MsPowerpoint, dan kemudian peserta diminta menyampaikan Bahan Pembelajaran Kompilasi lengkap dengan slide menggunakan MsPowerpoint. Hasil pelatihan menunjukkan bahwa, secara umum, Guru-guru yang mengikuti pelatihan masih belum maksimal menguasai materi: (1) Analisis Instruksional; (2) Mengembangkan Tujuan Instruksional Khusus (TIK); (3) Mengembangkan Instrumen Tes Hasil Belajar; (4) dan Mengembangkan Strategi Pembelajaran, sehingga tujuan pelatihan penyusunan Bahan pembelajaran Kompilasi terhadap 55 orang guru MPGP Teknik Elektronika yang dilakukan di SMK Negeri 1 cibinong Bogor belum dapat tercapai maksimal.